The Life, Achievements and Legacy of a Great Canadian Investigator: Professor Boris Petrovich Babkin (1877–1950) - Ivan T Beck (Canadian Journal of Gastroenterology)
The present paper reviews the life and achievements of Professor Boris Petrovich Babkin (MD DSc LLD). History is only worth writing about if it teaches us about the future; therefore, this historical review concludes by describing what today’s and future gastrointestinal physiologists could learn from Dr Babkin’s life.